IMPROVING GRADE 4 STUDENTS’ SPEAKING PARTICIPATION THROUGH INTERACTIVE CLASSROOM STRATEGIES - Muslimaxon, Toshtemirova (Research Focus International Scientific Journal, 2026)
In recent years, students’ participation in speaking activities has become both essential and challenging, as many learners struggle to express themselves orally in English. Although a number of studies have addressed this issue, some teachers still face difficulties in finding effective strategies to engage students in speaking tasks, especially in 4th and 5th grades where learners are expected to complete more speaking exercises during lessons. The main aim of this study is to investigate the reasons behind students’ low participation in speaking activities and to identify effective classroom strategies to improve their engagement. The study employed classroom-based action research. The participants consisted of 22 fourth-grade students from School No. 15 in Shahrihan district, Andijan region. Data were collected through classroom observations, student questionnaires, and informal conversations with colleagues. After data collection, all information was carefully analyzed using descriptive methods. The findings revealed that initially only a small number of students actively participated in speaking activities while some learners did not want to do speaking exercises because of shyness, lack of vocabulary and fear of making mistakes. However, after implementing interactive strategies such as pair work group work, the “Find a Friend” activity, a speaking dice game, and group storytelling, the number of active participants increased significantly. The results also showed that students became more confident, motivated, and willing to speak when they were engaged in interactive and collaborative tasks. This study can be useful for teachers who face similar challenges, as it highlights effective strategies for improving students’ speaking participation. In conclusion, creating a supportive and interactive classroom environment helps enhance students’ confidence and develop their speaking skills more effectively.